Leiomyoma of the Female Urethra—A Rare Tumor: Case Report and Review of the Literature - Mrinal Pahwa; Yusuf Saifee; Archna R. Pahwa; Manu Gupta (Case Reports in Urology)
Leiomyoma is a benign smooth muscle tumor which is rarely found in urethra. Only a handful of cases have been reported in the literature. We hereby report a case of urethral leiomyoma in a twenty-seven-year-old female who presented with intermittent hematuria. Mass was completely excised with a rim of normal tissue. Patient remained asymptomatic with no evidence of recurrence in followup.